The Dynamization Of Creative Economy Development In The Coastal Area Of Jeneponto Regency - Saripuddin; Muhammad Sirajuddin; Maksud Hakim (CV Putra Publisher, 2026)
The creative economy has become a strategic pillar for regional development, especially in coastal areas with distinctive cultural and natural resources. However, the dynamization—referring to the accelerated growth, adaptability, and sustained momentum—of creative economy development in the coastal periphery remains underexplored. This study examines the determinants influencing the dynamization of the creative economy in the coastal zone of Jeneponto Regency, South Sulawesi, Indonesia. A quantitative survey was conducted among 210 creative economy actors selected through stratified random sampling across four coastal sub-districts. Data were collected via a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital technology adoption, innovation capability, and government support exhibit the strongest positive effects on creative economy dynamization, while infrastructure and social capital show moderate but significant influences. Human capital and market access, although positive, had weaker direct effects. The structural model accounts for 67.8% of the variance in dynamization. These results underscore the necessity of a technology-enabled, innovation-driven, and institutionally supported ecosystem to accelerate creative economy transformation in coastal Jeneponto. The study contributes empirical insights for policymakers aiming to revitalize peripheral maritime economies through creative industry interventions.